Sarcopenia of thoracic muscle mass is not a risk factor for survival in lung transplant recipients - Lee, Seokkee; Paik, Hyo Chae; Haam, Seok Jin; Lee, Chang Young; Nam, Kyung Sik; Jung, Hee Suk; Do, Young Woo; Shu, Jee Won; Lee, Jin Gu (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: In lung transplantation (LTx), patients with thoracic muscle sarcopenia may have to require longer to recovery. We measured thoracic muscle volume by using the cross sectional area (CSA) and assessed its effect on early outcomes after LTx. Methods: A retrospective analysis was conducted to evaluate the effect of thoracic sarcopenia in patients undergoing LTx between January 2010 and July 2015. The lowest CSA quartile (Q1) was defined as sarcopenia. Results: In total, 109 patients were enrolled. The mean CSA was 58.24±15.82 cm2. Patients in the highest CSA quartile were more likely to be male (92.6% vs. 17.9%, P